2012
DOI: 10.5334/ijic.845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caregiver support interventions for informal caregivers of community-dwelling frail elderly: a systematic review

Abstract: IntroductionInformal caregivers are important resources for community-dwelling frail elderly. But caring can be challenging. To be able to provide long-term care to the elderly, informal caregivers need to be supported as well. The aim of this study is to review the current best evidence on the effectiveness of different types of support services targeting informal caregivers of community-dwelling frail elderly.MethodsA systematic literature search was performed in Medline, PsychINFO, Ovid Nursing Database, Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 26 publications
2
131
1
2
Order By: Relevance
“…Although many interventions demonstrated positive impacts on different outcomes such as burden [22,23], quality of life of the caregiver [24], and delay in hospitalization [25]; other similar studies did not find the same benefits [26][27][28]. Inconsistency of the current findings can be explained by the methodological issues caused by the complex nature of this type of research, e.g., [4,[29][30][31][32][33][34][35], such as: different duration of interventions, different intensity and characteristics of interventions, and the variety of caregivers and care-recipients characteristics. Additionally, these interventions often suffer from insufficient statistical power, short follow-up periods, and the use of various instruments to measure outcomes.…”
Section: Introductioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Although many interventions demonstrated positive impacts on different outcomes such as burden [22,23], quality of life of the caregiver [24], and delay in hospitalization [25]; other similar studies did not find the same benefits [26][27][28]. Inconsistency of the current findings can be explained by the methodological issues caused by the complex nature of this type of research, e.g., [4,[29][30][31][32][33][34][35], such as: different duration of interventions, different intensity and characteristics of interventions, and the variety of caregivers and care-recipients characteristics. Additionally, these interventions often suffer from insufficient statistical power, short follow-up periods, and the use of various instruments to measure outcomes.…”
Section: Introductioncontrasting
confidence: 47%
“…Despite several previous reviews concluded that the interventions under study are overall effective in decreasing or increasing specific outcomes that improve well-being (e.g., depression, self-efficacy), our opinion is that these overall conclusions should be made cautiously due to inconclusive results often caused by methodological issues as has been discussed in other comparable reviews, e.g., [11,12,30,33,37].…”
Section: Methodsological Issuesmentioning
confidence: 74%
See 1 more Smart Citation
“…1 The majority of these older adults are cared for by informal caregivers such as family or friends in the community. 2 In the United States, approximately 43.5 million informal caregivers provide care to older adults with chronic disease. 3 In Europe, 125 million people serve as informal caregivers for people with functional limitations in performing activities of daily living (ADL).…”
Section: Introductionmentioning
confidence: 99%
“…[37] A decrease in number of readmissions is presenting, as a result of heart failure education as part of heart failure programs. Despite the development of heart failure programs, the level adherence to prescribed medications, low-sodium diets and exercise remains lower than needed.…”
Section: Facilitating Experiencesmentioning
confidence: 99%